You would use the POINT SLOPE FORMULA and the Slope Formula
which is as follows ...
slope formula : ![\frac{y_{2}-y_{1} }{x_{2}-x_{1} }](https://tex.z-dn.net/?f=%5Cfrac%7By_%7B2%7D-y_%7B1%7D%20%20%7D%7Bx_%7B2%7D-x_%7B1%7D%20%20%7D)
point slope formula: ![y - y_{1} = m(x - x_{1} )](https://tex.z-dn.net/?f=y%20-%20y_%7B1%7D%20%3D%20m%28x%20-%20x_%7B1%7D%20%29)
Answer:
Step-by-step explanation:
Permutation is the ways in which a fixed group or members that can be arranged or ordered and combinations are used when a smaller group has to be chosen from a larger group.
Examples:
<u>Permutation: </u>How many unique combinations of the word MAHNOOR can be formed when the letters will be scrambled
2. In what order or arrangements five people can be seated in the front row?
The number of people are fixed, we have to find the order.
<u>Combination:</u> Choosing two cards from a deck of 52 cards. We are choosing a small group from a larger group of all cards.
2. Choosing 4 students from a class to take part in the competition.
The selection can be made in multiple ways ..
Answer:
B. -76-7C
Step-by-step explanation:
-6-7(c+10)
Distribute the 7
-6-7c-70
Combine like terms
-7c-76
Answer:
The equation in the standard form is
![y+2x=5](https://tex.z-dn.net/?f=y%2B2x%3D5)
Step-by-step explanation:
Given the points
Finding the slope between (6, -7) and (4, -3)
![\left(x_1,\:y_1\right)=\left(6,\:-7\right),\:\left(x_2,\:y_2\right)=\left(4,\:-3\right)](https://tex.z-dn.net/?f=%5Cleft%28x_1%2C%5C%3Ay_1%5Cright%29%3D%5Cleft%286%2C%5C%3A-7%5Cright%29%2C%5C%3A%5Cleft%28x_2%2C%5C%3Ay_2%5Cright%29%3D%5Cleft%284%2C%5C%3A-3%5Cright%29)
![\mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cmathrm%7BSlope%7D%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
![m=\frac{-3-\left(-7\right)}{4-6}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-3-%5Cleft%28-7%5Cright%29%7D%7B4-6%7D)
![m=-2](https://tex.z-dn.net/?f=m%3D-2)
As the point-slope form is defined as
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
substituting the values m = -2 and the point (6, -7)
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
![y-\left(-7\right)=-2\left(x-6\right)](https://tex.z-dn.net/?f=y-%5Cleft%28-7%5Cright%29%3D-2%5Cleft%28x-6%5Cright%29)
Writing the equation in the standard form form
As we know that the equation in the standard form is
![Ax+By=C](https://tex.z-dn.net/?f=Ax%2BBy%3DC)
where x and y are variables and A, B and C are constants
converting the equation in standard form
![y-\left(-7\right)=-2\left(x-6\right)](https://tex.z-dn.net/?f=y-%5Cleft%28-7%5Cright%29%3D-2%5Cleft%28x-6%5Cright%29)
![y+7=-2\left(x-6\right)](https://tex.z-dn.net/?f=y%2B7%3D-2%5Cleft%28x-6%5Cright%29)
subtract 7 from both sides
![y+7-7=-2\left(x-6\right)-7](https://tex.z-dn.net/?f=y%2B7-7%3D-2%5Cleft%28x-6%5Cright%29-7)
![y=-2x+5](https://tex.z-dn.net/?f=y%3D-2x%2B5)
![y+2x=5](https://tex.z-dn.net/?f=y%2B2x%3D5)
Therefore, the equation in the standard form is
![y+2x=5](https://tex.z-dn.net/?f=y%2B2x%3D5)
Answer:
a is 3x
b is 6(8y-5) and 6x8y-6x5
Step-by-step explanation:
first a is 3x
b is 6(8y-5) 6x8y-6x5